PEMBUATAN GAME PERTEMPURAN SURABAYA - Sanchez Haryon Rohani; Jeanny Pragantha (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Pertempuran Surabaya game is an educational games that aims to increase knowledge about the history of struggle for Indonesia’s independence day on November 10, 1945. This game provides knowledge about the history of Indonesian independence to the players. This game can only played on a windows operating system. Pertempuran Surabaya game was created using Adobe Flash CS 6 software using Actionscript 3.0.This game consist  of 10 mini games. Each games have different type of games which has different gameplay and stages. By testing phase, it can be concluded that Pertempuran Surabaya  game has good quality and is running well. By playing the games, players knowledge about history of Pertempuran Surabaya can increase . Key wordsIndonesia, Pertempuran Surabaya, minigame, tradisional